Modern problems of repeated criminality. Socio-psychological aspect - Y.E. Suslov; A.F. Fedorov; A.V. Bespalova (Психология и право)
Current data of official statistics show a steady decline in the number of crimes committed in our country. There is a general humanistic vector of development of the domestic law enforcement system and, in particular, the system of execution of punishments, which is expressed in the reduction in the number of persons both criminally prosecuted and sentenced to real imprisonment for a certain period of time, the creation and development of the institute of probation as a system of support for those released from prison. At the same time, the problem of crime in general and repeat crime in particular does not lose its relevance. The presented work analyzes the data of scientific research devoted to the study of repeat crime. Special emphasis is made on the group of convicts who repeatedly served their sentences in places of deprivation of liberty or previously served their sentences in educational colonies of the criminal-executive system of the Russian Federation. Through the prism of the study of this sample, the issue of the effectiveness of the system of correction of persons who have committed crimes is analyzed from a psychological point of view. Key words: correction, punishment, youth, convicts, repeated criminality, criminal behavior, criminality, recidivism, penal system of the Russian Federation